Overexpression of glyoxalase-I in bovine endothelial cells inhibits intracellular advanced glycation endproduct formation and prevents hyperglycemia-induced increases in macromolecular endocytosis. - Shinohara, M (1998)
Methylglyoxal (MG), a dicarbonyl compound produced by the fragmentation of triose phosphates, forms advanced glycation endproducts (AGEs) in vitro. Glyoxalase-I catalyzes the conversion of MG to S-D-lactoylglutathione, which in turn is converted to D-lactate by glyoxalase-II. To evaluate directly the effect of glyoxalase-I activity on intracellular AGE formation, GM7373 endothelial cells that stably express human glyoxalase-I were generated. Glyoxalase-I activity in these cells was increased 28-fold compared to neo-transfected control cells (21.80+/-0.1 vs. 0. 76+/-0.02 micromol/min/mg protein, n = 3, P < 0.001). In neo-transfected cells, 30 mM glucose incubation increased MG and D-lactate concentration approximately twofold above 5 MM (35.5+/-5.8 vs. 19.6+/-1.6, P < 0.02, n = 3, and 21.0+/-1.3 vs. 10.0+/-1.2 pmol/ 10(6) cells, n = 3, P < 0.001, respectively). In contrast, in glyoxalase-I-transfected cells, 30 mM glucose incubation did not increase MG concentration at all, while increasing the enzymatic product D-lactate by > 10-fold (18.9+/-3.2 vs. 18.4+/- 5.8, n = 3, P = NS, and 107.1+/-9.0 vs. 9.4+/-0 pmol/10(6) cells, n = 3, P < 0.001, respectively). After exposure to 30 mM glucose, intracellular AGE formation in neo cells was increased 13.6-fold (2.58+/-0.15 vs. 0.19+/-0.03 total absorbance units, n = 3, P < 0.001). Concomitant with increased intracellular AGEs, macromolecular endocytosis by these cells was increased 2.2-fold. Overexpression of glyoxalase-I completely prevented both hyperglycemia-induced AGE formation and increased macromolecular endocytosis.